Low rates of rock organic carbon oxidation and anthropogenic cycling of rhenium in a slowly denuding landscape - Ogrič, M; Dellinger, M; Grant, KE; Galy, V; Gu, X; Brantley, SL; Hilton, RG (Wiley, 2023)
The oxidation of petrogenic organic carbon (OCpetro) is a source of carbon dioxide to the atmosphere over geological timescales. The rates of OCpetro oxidation in locations that experience low rates of denudation remain poorly constrained, despite these landscapes dominating Earth’s continental surface area. Here, we track OCpetro oxidation using radiocarbon and the trace element rhenium (Re) in the deep weathering profiles, soils and stream waters of the Susquehanna Shale Hills Critical Zone Observatory (PA, USA). In a ridge-top borehole, radiocarbon measurements reveal the presence of a broad OCpetro weathering front, with a first order assessment of ~40% loss occurring over ~6 m. However, the low OCpetro concentration (<0.05 wt.%) and inputs of radiocarbon throughout the deepest parts of the profile complicate the assessment of OCpetro loss. The OCpetro weathering front coincides with a zone of Re depletion (~90% loss), and we estimate that >80% of Re in the rock is associated with OCpetro, based on Re/Na and Re/S ratios. Using estimates of long-term denudation rates, the observed OCpetro loss and the Re proxy are equivalent to a low OCpetro oxidation yield of <1.7×10-2 tC km-2 yr-1. This is consistent with the low OCpetro concentrations and low denudation rates at this location. In addition, we find the surface cycle of Re is decoupled from that of deep weathering, with an enrichment of Re in surface soils and elevated Re concentrations in stream water, precipitation, and shallow groundwater. A mass balance model shows that this can be explained by a historical anthropogenic contribution of Re through atmospheric deposition. We estimate that the topsoil Re pool could take decades to centuries to deplete and call for a renewed focus on anthropogenic perturbation of the surface Re cycle in low denudation rate settings.